PRINSIP DUE PROCESS OF LAW DALAM SISTEM PERADILAN PIDANA ANAK MENURUT UNDANG-UNDANG NO.3 TAHUN 1997 TENTANG PENGADILAN ANAK - Supriyanta - - (Exsplorasi, 2011)
ABSTRACTPrinciple of due process of law related with child criminal have been regulated in UU No.8 Tahun 1981 about Kitab Undang-Undang Hukum Acara Pidana (KUHAP) jo UU No.3 Tahun 1997 about Pengadilan Anak. In KUHAP, there are ten principles must be basic in criminal justice system and in UU No.3 Tahun 1997 requirment for criminal justice system to child criminal likes special investigator, prosecutor , and judge. Beside that there is society conceling from Social Departement. Investigation of this case by familiar, have to spiltsing from adult criminal, ect.Key words: Due Process of Law, UU No.8 Tahun 1981 tentang KUHAP,UU No.3 Tahun1997 tentang Pengadilan Anak.